CE: Original Research. (December 2016) - Chang, Shu-Hung; Chen, Miao-Chuan; Chien, Nai-Hui; Wu, Li-Yu
Abstract : N/A: Background: As it is in many other developed countries, obesity is a growing health concern in Taiwan, affecting nearly 20% of the adult population. Obesity can increase the risk of developing metabolic syndrome, diabetes, and cardiovascular disease. Recent data indicate that the prevalence of metabolic syndrome in Taiwan is 25.5%. Yet some overweight and obese individuals have normal metabolic profiles. It's not clear why some overweight or obese people remain metabolically healthy while others do not. Purpose: The purpose of this study was to examine lifestyle risk factors for metabolic syndrome in people who are overweight or obese. We were particularly interested in distinguishing those lifestyle factors associated with metabolic health in this population. Methods: Data collected from community-based physical examinations in northern Taiwan were used for this cross-sectional study. A survey was conducted from 2013 to 2014. We collected data on demographic variables, clinically pertinent measures (weight; height; waist circumference; blood pressure; and levels of fasting blood glucose, triglycerides, and high-density lipoprotein cholesterol), and lifestyle factors (smoking, drinking, exercise, and dietary habits). To analyze the data, we used percentage, mean, standard deviation, χ 2 test, independent t test, the Fisher exact test, phi correlation, and logistic regression. Results: The overall prevalence of metabolic syndrome among all 734 participants was 36.4%. For the normal weight, overweight, and obese groups, the prevalence of metabolic syndrome was 12.4%, 36.4%, and 61.6%, respectively. The results of logistic regression showed, however, that obese individuals who exercised regularly and ate sufficient amounts of fruit were less likely to have metabolic syndrome, and that overweight individuals who were nonsmokers and ate sufficient amounts of vegetables were also less likely to have metabolic syndrome. Conclusions: Lifestyle factors may significantly affect the development of metabolic syndrome in people who are overweight or obese. Our findings indicate that practicing healthy lifestyle behaviors may be the best way to prevent metabolic syndrome. Public health interventions promoting smoking cessation, regular exercise, and good dietary habits can be created and conducted at relatively low cost. At the community level, all nurses can prioritize such interventions for their overweight and obese patients. Abstract : The authors of this study examined lifestyle risk factors for metabolic syndrome—such as dietary and exercise habits—in people who are overweight or obese, aiming to distinguish those lifestyle factors associated with metabolic health in this population.